The correlation of the value of amanah and islamic pricing theory with customer satisfaction and its implication on customer loyalty in hajj and umrah service products in Surabaya - Dina Fitrisia Septiarini, NIDN. 0719097702 (University of Bahrain, 2017)
In the highly competitive business of umrah and hajj services, every enterprise must find ways to maintain or develop customer satisfaction and customer loyalty, not only for the short period but also in the long term. The value of amanah and Islamic Pricing Theory are some of the factors which are influential in developing customer satisfaction and loyalty. This study aimed to find out the correlation between the value of amanah and Islamic Pricing Theory with customer satisfaction and their implication on customer loyalty. The approach employed in this research was quantitative using PLS analysis technique. There were three variables: which are independent, dependent, and intervening variables. The independent variables were the value of amanah and Islamic Pricing Theory while the dependent variable was customer satisfaction, and the intervening variable was customer loyalty. The subjects of the research were 100 customers that had used agencies providing umrah and/or hajj services in Surabaya. The data analysis instrument applied was SPSS. From this research, it can be concluded that Islamic Pricing Theory significantly affects customer satisfaction. This is indicated by the value of T Statistics reaching 6.666900 and shows positive correlation which is evident from the positive value of path coefficient estimation. In addition, customer satisfaction significantly affects customer loyalty as shown by the value of T Statistics reaching 3.562147 and has positive correlation. The concept of amanah does not provide a significant effect on customer satisfaction as indicated by the value of T Statistics of 1.617197. Additionally, the belief on Amanah does not provide a significant effect on customer loyalty as indicated by the value of T Statistics of 1.057132 belief is amanuh.